The Influence of Salesmanship Competency and Service Quality on Competitiveness and Business Performance in Mitra Karya Sukses - Lina Maretasari; Slamet Ahmadi (Yayasan Amerta Insan Unggul, 2024)
In the midst of increasingly fierce business competition, building material distributors in East Bogor face great challenges in maintaining and increasing their market share. Building material distributors, such as Mitra Karya Sukses , must compete not only on price, but also on product quality, service, and speed of delivery. To survive and thrive in this competitive market, companies are required to have competent salesmanship and superior service quality in order to create strong competitiveness that will ultimately improve the company's business performance. This study aims to analyze the effect of salesmanship competence and service quality on business performance through competitiveness. This study was conducted at Mitra Karya Sukses , a distributor of building materials located at Jalan Gas Alam, Wanaherang Village, Gunung Putri District, Bogor Regency. This research uses a quantitative approach with data collection methods in the form of primary data obtained through distributing questionnaires to 87 customers of Mitra Karya Sukses and secondary data in the form of sales reports as supporting data. The data obtained were analyzed using various statistical techniques, including descriptive statistical analysis to describe the characteristics of respondents and research variables, measurement model evaluation (outer model), structural model evaluation (inner model) and hypothesis testing to determine direct and indirect effects (the role of mediating variables). The results of this study indicate that salesmanship competence and service quality each have a positive and significant effect on competitiveness and business performance, competitiveness has a positive and significant effect on business performance, while the competitiveness variable does not play a role in mediating the effect of salesmanship competence and service quality on business performance at Mitra Karya Sukses . The independent variable is able to explain the dependent variable by 70.5%.